Valorization of Almond (Prunus serotina) by Obtaining Bioactive Compounds - Gallardo-Rivera, Claudia T.; Lu, Analía; Treviño-Garza, Mayra Z.; García-Márquez, Eristeo; Amaya-Guerra, Carlos; Aguilera, Carlos; Báez-González, Juan G. (Frontiers in Nutrition, 2021)
The Capulin almond is a seed of the Prunus serotina (var. capuli) that belongs to the Rosaceae family. In this study, the valorization of the Capulin almond was performed by extracting antioxidants contained in the shell, paste, and oil (extracted by manual cold pressing process) of Prunus serotina treated with methanol, ethanol, acetone, and acidified water (pH 4) in a ratio of 1:5 (w/v). Total phenols were performed using the Folin-Ciocalteu method and expressed as gallic acid equivalents (GAE), antioxidant activity was determined by ABTS and DPPH methods and expressed as Trolox equivalents (TE). Finally, the total flavonoids were determined using a catechin calibration curve and reported as catechin equivalents (CE). The highest extraction of total phenols in shell was obtained with methanol (1.65 mg GAE/g sample) and the lowest using acidified water (0.97 mg GAE/g sample). However, extraction with acidified water favored this process in the paste (1.42 mg GAE/g sample), while the use of solvents did not influence it significantly (0.72 to 0.79 mg GAE/g sample). Regarding the total flavonoids, the values for the shell, paste, and oil were of 0.37, 0.78, and 0.34 mg CE/g sample, respectively, while that corresponding to the antioxidant activity evaluated with ABTS and DPPH were of 1527.78, 1229.17, 18894.44 M TE/g, and, 568.45, 562.5 and 4369.05 mM TE/g sample, respectively. Finally, our results suggest that by-products such as the shell, paste, and oil obtained from Prunus serotina (var. capuli) represent a potential alternative for the recovery of bioactive compounds with antioxidant activity such as phenolic compounds and flavonoids.